High-throughput sequencing method to study the dynamic changes of microbial communities in second-generation fermented lettuce. Issue 1 (March 2021) - Zhang, Yao; Chen, Zhidi; Wang, Xinyu; Li, Qingwen; Gao, Xiuzhi; Yi, Xinxin; Ma, Yumeng
Abstract: Pickle has been loved by consumers since ancient times because of its unique taste, strong flavor, simple process and long shelf life. Complex microbial succession activities promote the fermentation process of pickle. In this paper, high-throughput sequencing methods were used to study the bacterial microbial dynamics of the second-round fermentation lettuce artificially inoculated with Lactobacillus . The results showed that as the fermentation progressed, at the bacterial genus level, Lactobacillus are the dominant genus in the fermentation process. In the late fermentation stage, the dynamic changes of microorganisms tend to be stable. These results provide ideas and new strategies for the development of pickle products using lettuce as the main vegetable raw material.